Analysis of the Application of Transformational Leadership Style in Increasing the Effectiveness of Employee Duties Implementation at the regional Secretariat of Wajo Regency - Sitti Aminah; Syamsiar Syamsiar; Nur Ulfiani As’Ad (International Journal of Social Science and Humanity, 2026)
This study to analyze the importance of the application of transformational leadership styles in improving the effectiveness of employe task implementation at the Wajo Regency Regional Secretariat. Considering role of the Regional Secretariat as a center for coordinating government administration, leadership that is able to inspire and motivate employees to achieve optimal performance is need. This study uses a qualitative approach with descriptive methods. Data collection was conducted through observation, in-depth inteviewa, and documentation. Informants were determined using a purposive sampling technique, consisting of leadership elements (Regional Secretary, Assistant for General Administration of the Regional Secretaist, Head of General Affairs, Head of Organization, Head of Administration, and Head of General Affairs and Finance). Data analysis was conducted through an interactive model that includes data collection, data condensation, Data presentation, and conclution drawing. The result of the study indicate that leaders at the Wajo Regency Regional Secretariat heve implemented four dimensions of transformational leadership well,namely: 1) Individual Attention, 2) Intellctual Simulstion, (encouragement to innovative, and 4)Idealized Influence. The implementation of this leadership style has been proven to increase the effectiveness of employe task execution, as evidenced by improved discipline, work motivation, the ability to adapt to regulatory changes, and more timely completion of work programs.